A Real-Time IOT Monitoring and Safety Cutoff System for Electric Vehicle Batteries Using the BLYNK Platform - jefri Lianda; Agustiawan; Adam; Johny Custer; Rindilla Antika; Marzuarman (JURNAL TEKNIK INFORMATIKA, 2026)
This paper presents the design and implementation of a 58-volt LiFePO₄ battery voltage management system for electric vehicles, featuring remote monitoring and control via the Blynk application. The system continuously monitors battery voltage levels and enables control through a Solid-State Relay (SSR) connected to a NodeMCU ESP8266 microcontroller. Through the Blynk interface, users can view real-time voltage readings along with the corresponding battery capacity percentage. The NodeMCU ESP8266 demonstrated reliable performance throughout all test phases, maintaining a stable internet connection. The average voltage measurement deviation displayed on the Blynk application was approximately 0.74%. The SSR is configured to disconnect the vehicle’s power supply when the battery voltage reaches around 46.3 volts or when the battery percentage decreases to 0.16%. This disconnection can be triggered manually through the Blynk application or automatically by the SSR. The disconnection process can be carried out through the Blynk application or automatically via the Solid State Relay (SSR). Remote disconnection via the Blynk application serves as an additional safety measure activated when suspicious conditions or activities are detected. This mechanism safeguards the battery from excessive discharge, promoting better performance and extending its service life by cutting off the load at critical limits.